Related Factors to Streptococcus pneumoniae Invasive Infection and Clinical Manifestations: The Potential Role of Nasopharyngeal Microbiome - Dietl, Beatriz; Henares, Desirée; Boix-Palop, Lucía; Muñoz-Almagro, Carmen; Garau, Javier; Calbo, Esther (Frontiers in Medicine, 2021)
Lower respiratory infections (including pneumonia) are one of the most important causes of death worldwide. Streptococcus pneumoniae might colonize the upper respiratory tract of children and adults, can cause a wide spectrum of disease and is the main aetiological agent of community-acquired pneumonia (CAP). In the last decades, many factors related to the host, the microorganism and the antibiotic therapy have been assessed to identify risk factors for the development of invasive pneumococcal disease (IPD). Nevertheless, these factors themselves do not explain the risk of developing disease or its severity. Recently, some studies have focused on the importance of nasopharyngeal (NP) microbiome and its association with respiratory health. This review presents the evidence regarding the potential role of NP microbiome in the development of IPD known to date.